A multi-scale examination of the distribution and habitat use patterns of the regal fritillary - McCullough, Kelsey (Kansas State University, 2016)
The regal fritillary (Speyeria idalia) was once an abundant butterfly species of North American prairie communities. Despite its once broad geographic distribution, populations have declined by ~99% in the prairie region for reasons that are poorly understood. The rapid, range-wide declines and persistent threats to extant populations from habitat loss and mismanagement prompted the U.S. Fish and Wildlife Service to initiate a species status review of the regal fritillary as a potential candidate for listing under the endangered species act in September 2015. Due to the uncertain status and contention regarding the effects of management practices (i.e., burning, grazing, and haying) on regal fritillary, my research objectives were to assess the effects of management practices and habitat features on the distribution and density of regal fritillary and their preferred larval host plant for the Midwest, prairie violet (Viola pedatifida). I generated species distribution models (SDM) of prairie violet to readily identify potential areas across the landscape containing patches of host plants and subsequently facilitate the location of regal fritillary larvae. The SDM produced maps of the probabilistic occurrence distribution of prairie violet throughout my study area and highlighted habitat features and management practices important to the occurrence of prairie violet. The seven final variables used to create the SDM and identified as important to the occurrence of prairie violet were elevation, slope, hillshade, slope position, land cover type, soil type, and average fire frequency. Using the SDM for prairie violet, I located eight areas to conduct surveys for regal fritillary larvae that were managed using various management (grazing and haying) regimes and fire-return intervals (low ≥ 10 years, moderate 3-5 years, and high 1-2 years). I used a binomial generalized linear model to determine the effects of management, host plant density, months since burn, and the interaction between months since burn and management on the occurrence distribution of regal fritillary larvae. My results indicate that greater host plant density and short fire-return intervals are important to the occurrence of regal fritillary larvae and, despite current management recommendations, larvae may be negatively impacted by a lack of fire. Finally, I surveyed tracts of prairie with my study area using a distance sampling approach along line transects stratified by overall management (burned, grazed, and hayed) and fire-return interval (low ≥10 years, moderate 3-5 years, and high 1-2 years) for adult regal fritillary. My results indicated that adult density was at least 84% greater in areas that received moderate fire-return intervals and greatest in areas that were grazed and burned on a moderate fire-return interval. However, density estimates of adult regal fritillary did not differ among overall management practices (i.e., burned grazed, hayed). Additionally, adult density increased as percent cover of grass, litter, and prairie violets increased. In contrast, adult density decreased as percent cover of woody vegetation and forbs increased. These results support the use of prescribed fire in a shifting mosaic or patch-burning practice as a viable management strategy for maintaining and conserving regal fritillary populations within the Flint Hills region.
Keywords: Regal fritillary; Speyeria idalia; Tallgrass prairie; Management; Great Plains; Butterfly